Retentive properties of five different luting cements on base and noble metal copings - (:unkn) unknown (MOSBY, INC, 2002)
Statement of problem. The retention of indirectly fabricated restorations can be compromised by short or over-tapered tooth preparations. Purpose. The aim of this study was to evaluate the retentive properties of 5 different luting cements on base and noble metal copings to short and over-tapered preparations. Material and methods. Eighty extracted mandibular premolars were prepared to receive full cast copings with a flat occlusal surface, 33degrees taper, and 3-mm axial length. Half of the standardized metal copings were cast in an AuAgPd alloy, whereas the other half were cast in an NiCr alloy. Cementation was performed with 5 different luting cements through use of 5 kg of pressure in 90% relative humidity. Specimens were stored in distilled water at 37degreesC for 24 hours and thermocycled between 5degreesC and 55degreesC for 5000 cycles, with a dwell time of 30 seconds. After thermocycling, vertical tensile force was applied in a Zwick universal testing machine with a constant speed of I mm/min until separation,vas noted. A 2-factor analysis of variance was used to analyze the data, with a significance level of alpha = .05. Results. Mean dislodgement forces for AuAgPd crowns and NiCr crowns were 120.88 N and 143.09 N, respectively, for zinc phosphate cement; 135.45 N and 150.38 N for Principle; 145.88 N and 220.71 N for Meron; 276.85 N and 225.61 N for Avanto; and 300.92 N and 381.02 N for Fuji Plus. Conclusion. Within the limitations of this study, Fuji Plus and Avanto showed significantly higher retentive strengths for AuAgPd copings in comparison to the other cements tested (P < .05). The retentive strength of Fuji Plus was significantly higher than those of the other cements tested with NiCr copings (P < .05).
Keywords: GLASS-IONOMER; CROWN RETENTION; BOND STRENGTHS; RESIN CEMENT; IN-VITRO; ENAMEL; DENTIN; AGENTS; ADHESION; BRIDGES